ANALISIS SISTEM DAN PROSEDUR REKRUTMEN CALON SUMBER DAYA MANUSIA PT HERO SUPERMARKET, TBK JAKARTA - Widjaya, Oey Hannes; Utama, Louis (Jurnal Ekonomi, 2017)
This study was conducted to determine Systems and Procedures Recruitment Candidates HR conducted at PT Hero Supermarket, to find weaknesses in systems and procedures Recruitment conducted at PT Hero Supermarket, to know the systems and procedures Recruitment Candidates human resources for this cause problems for the company to look for a proper solution in the Systems and Procedures Recruitment conducted at PT Hero Supermarket. The object of this research study is PT Hero Supermarket Tbk. engaged in the supermarket industry retailers (supermarket) which was established in 1971 and is located on Jalan Gatot Subroto Kav 64 177 A South Jakarta, Indonesia. Subject Research and Systems Analysis Candidate Recruitment Procedures HR. Methods of data collection by interview and observation. Data processing techniques using the editing, coding, tabulation and komputerasisasi. The analysis and discussion of the results obtained by computerized namely Flowchart Flowchart Candidate Filing HR Recruitment, HR Candidate Recruitment Planning Flowchart, Flowchart Ad Candidate Recruitment HR, Cover Letters Candidate Selection Flowchart human resources PT Hero Supermarket Tbk